Involvement of Women in Handloom Segment: An Empirical Study With Reference To Krishna District, Andhra Pradesh - Rao, D.Srinivasa; Sreedhar, N.; Kumar, B. Ravi (American Economic & Social Review, 2018)
The handloom is a traditional craft work of India and it provides employment opportunities to lakhs of people in the rural and urban areas of our country. In the world women constitutes approximately 50% of the total population but society is still male dominated one. In India women contributed substantially to the economic growth of the country.The relationship between gender and the economy has considerable importance in Indian society. In general attitude of the people women are second grade citizens and they are makers of food, pickles, papads, masalas etc,. But their role is very important in every economic activity, either it is household work or cultivation or industry or service sector etc,. Like the other sectors the role of women weavers is very much important in handloom sector. Handloom sector is unique in India. The handloom weaving is household profession, followed by generations. In these households, women play an important role. Handloom sector is the only manufacturing sector in which women producing for women.